Achieving IoT nirvana by protecting cellular networks. Issue 8 (August 2019) - Ghalaieny, Dawood
Abstract : The next several billion cellular connections will not connect people. They will connect devices, sensors, measurement tools and machines to create a complex Internet of Things (IoT). Despite the success of cellular technology to date – two thirds of the world's population is now connected – IoT is expected to be the next goldrush for the industry. Little wonder then that companies large and small are rushing headlong into the opportunity. The next several billion cellular connections will not connect people. They will connect devices, sensors, measurement tools and machines to create a complex Internet of Things (IoT). The IoT can undoubtedly be a force for good. Combined with machine learning techniques, it will deliver business efficiencies and insight that can transform industries. However, today's cellular networks are built on technology that is hardly fit for purpose in protecting voice and data from data breaches, cyber attacks and hacking, says Dawood Ghalaieny of Cellusys.